Function and Therapeutic Potential of Mesenchymal Stem Cells in Atherosclerosis - Li, Feifei; Guo, Xia; Chen, Shi-You (Frontiers in Cardiovascular Medicine, 2017)
Atherosclerosis is a complicated disorder and largely attributable to dyslipidaemia and chronic inflammation. Despite therapeutic advances over past decades, atherosclerosis remains the leading cause of mortality worldwide. Due to their capability of immunomodulation and tissue regeneration, mesenchymal stem cells (MSCs) have evolved as an attractive therapeutic agent in various diseases including atherosclerosis. Accumulating evidences support the protective role of MSCs in all stages of atherosclerosis. In this mini-review, we highlight the current understanding of MSCs including their characteristics such as molecular markers, tissue distribution, migratory property, and immune-modulatory competence, etc. We also summarize MSC functions in animal models of atherosclerosis. MSC transplantation is able to modulate cytokine and chemokine secretion, reduce endothelial dysfunction, promote regulatory T cell function, decrease dyslipidemia, and stabilize vulnerable plaques during atherosclerosis development. In addition, MSCs may migrate to lesions where they develop into functional cells during atherosclerosis formation. Finally, the perspectives of MSCs in clinical atherosclerosis therapy are discussed.